Radiometric receiving complex and ways to reduce the radiometric measurements error - A. M. Pylypenko; I. K. Sunduchkov; V. V. Chmil; V. M. Chmil; P. O. Yatsyk (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature)
The authors formulate criteria for building a structural scheme and developing design and technological solutions for a reception complex for full-power compensation radiometers. The paper presents the results of development of the reception complex within the framework of equipping small telescopes created according to the program VLDI2010.